The Transitional Period of the Periodicals Format Shift - Fenton, Eileen Gifford; Schonfeld, Roger C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
One of the more dramatic shifts affecting libraries in the past decade has been the rapid pace of technological change. In particular, the ongoing transition from print to electronic periodicals has challenged librarians to rethink their strategies. While some effects of this change have been immediately apparent - greater breadth of material, easier access for users, exposure to new sources, publisher package deals, and open access - the broader outcomes on library operations remain unclear.